2015
DOI: 10.1007/978-3-319-11316-6
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Control Systems with Time-Delay and Stochastic Perturbation

Abstract: The series "Studies in Systems, Decision and Control" (SSDC) covers both new developments and advances, as well as the state of the art, in the various areas of broadly perceived systems, decision making and control-quickly, up to date and with a high quality. The intent is to cover the theory, applications, and perspectives on the state of the art and future developments relevant to systems, decision making, control, complex processes and related areas, as embedded in the fields of engineering, computer scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 174 publications
(260 reference statements)
0
7
0
Order By: Relevance
“…However, the application of NCS with its stochastic behavior introduced new challenges induced by the exchange of data through the network and the difficulty to ensure a correct and accomplish transmission of data between sensors, actuators, and controllers. From References 2 and 4, we conclude that the author's proposed scheme really improved the performances and stability conditions for the control system. Among these challenges, we can find the capacity of the network's communication, the disturbances introduced into the communication, the delays, and packet losses 9 .…”
Section: Introductionmentioning
confidence: 76%
“…However, the application of NCS with its stochastic behavior introduced new challenges induced by the exchange of data through the network and the difficulty to ensure a correct and accomplish transmission of data between sensors, actuators, and controllers. From References 2 and 4, we conclude that the author's proposed scheme really improved the performances and stability conditions for the control system. Among these challenges, we can find the capacity of the network's communication, the disturbances introduced into the communication, the delays, and packet losses 9 .…”
Section: Introductionmentioning
confidence: 76%
“…This block allows the bio-inspired algorithm, in this case CSO, to demonstrate its efficiency in the optimization of the control problem. Some works where the behavior of the problem with level of noise in the model is analyzed are [31,[58][59][60][61][62][63][64]. In this paper, two type of disturbances are considered in each model.…”
Section: Fuzzy Logic Controllermentioning
confidence: 99%
“…The whole proof is completed □. Remark 6 Once the scalar δ is provided, the inequalities in (49) can be directly solved by the convex‐optimum method in MATLAB. Several search methods for the scalar δ have been introduced in [30, 40]. The idea of [30] is chosen in this study, and the detailed process can be found in [30].…”
Section: Stability Analysis and Stabilisation Of Time‐delay Systemsmentioning
confidence: 99%